KETERAMPILAN MENYIMAK BERITA MENGGUNAKAN MEDIA AUDIO-VISUAL SISWA KELAS VIII SMPN 2 KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - ERNIS, PONI (Inovasi Pendidikan, 2017)
Background research is the condition of students who experience saturation in listening activities at the time of learning. Saturation is caused by several factors. 1. Interest and motivation to learn the students in the process of learning listening skills are low, 2. Less optimal media used by teachers to support the implementation of learning listening skills, 3. Teachers have not used audio-visual media such as the use of infokus in the learning process. Media that is an integral factor in learning can be an important factor in overcoming the problem. Quantitative research type descriptive method. The study population was 142 students consisting of six classes, and the sample was class VIII5 used by Cluster Random Sampling. The instrument for data retrieval is a written test of objective tests. The results of the study are generally quite good with an average of 94.043. Based on the indicators, (1) in determining what (what) the average score of students is 94.78 and is very good, (2) in determining who (who) the average score is 93.47 and is very good, (3) in determining why (why) the average score of students is 86.95 and is quite good, (4) in determining where (where) the average score of students is 94.78 and is very good, (5) in determining when (when) the average value of students is 98.86 and is considered perfect, and (6) in determining how (how) the average value of students is 100 and pertained perfect. Based on the research that has been done, audio-visual media suitable for news material, because it can improve student learning outcomes.Keywords: Listening, News, Audio-Visual